If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(-4a-5)+6a=-25-4a
We move all terms to the left:
3(-4a-5)+6a-(-25-4a)=0
We add all the numbers together, and all the variables
3(-4a-5)+6a-(-4a-25)=0
We add all the numbers together, and all the variables
6a+3(-4a-5)-(-4a-25)=0
We multiply parentheses
6a-12a-(-4a-25)-15=0
We get rid of parentheses
6a-12a+4a+25-15=0
We add all the numbers together, and all the variables
-2a+10=0
We move all terms containing a to the left, all other terms to the right
-2a=-10
a=-10/-2
a=+5
| –.5(2n+4)+6=–9+4(2n+1) | | y-(0.2y)=9.60 | | -7(6x-4)=-42x-28 | | x/7-10=x/7 | | 4x+5=2x^2 | | 11x+26=6x+176 | | -9=m/3-10 | | -3(-5+2x)+8=-4x+35 | | 6-2x=7x+50 | | 6.8-3m=26 | | -2=7-3f | | (0,4x)^2=1 | | 2x+954+2x=4580 | | 6/7x+15-8=31 | | 5-2(2-7x)=1-x | | 10+2c=20 | | -2.2m+6+7.3m=-3.5+5.1m+9.5 | | 2a=2^2 | | 19=4+3k | | x-954=4580 | | 3(x-3)-19=5x-2(x-1) | | x+x-2=176 | | 5x+20=20x-10 | | -4(7x-8)=116 | | -v+-5=-1 | | 0.07(7x+2)=0.49(x+7)-3.29 | | X+3y=41 | | 2(x+1)=1/3x+4 | | 14=4h+-2 | | 2x-954=4580 | | 6(3r+8)+6=126 | | 2x+954=4580 |